Pure Leydig cell tumor of the ovary in a premenopausal woman - Apelt-Alcalay, Daniela (2020)
Leydig cell tumors of the ovary are a rare type of sex cord-stromal tumors, corresponding to less than 0.1% of all ovarian neoplasms. With a low incidence and frequent false-negative imaging results, these tumors represent a diagnostic challenge. Although more common in menopause, cases have also been described in premenopausal women. The most common clinical feature is rapidly progressive virilization; over 75% of patients show signs of virilization due to testosterone overproduction. Serum testosterone concentration is the most useful marker for diagnosing androgen-secreting tumors of the ovary. Leydig cell tumors should always be considered in women of reproductive age with virilization symptoms. We present the case of a pure Leydig cell tumor of the ovary in a premenopausal woman.